Perimyocarditis Following COVID-19 Vaccination - Mariana Tinoco (SAGE Publishing, 2021)
A 39-year-old male was admitted in the emergency room with chest pain. He had been given the second dose of Pfizer–BioNTech COVID-19 vaccine 3 days before. The patient denied taking any other medication beyond the usual. He didn’t feel sick in the previous days/weeks. Laboratory studies revealed elevated serum levels of troponin and C-reactive protein. An autoantibody screen and a serologic panel to detect common viruses were negative. A cardiac MRI showed myocardial edema/inflammation and confirmed the diagnosis of perimyocarditis which was considered to be a consequence of COVID-19 vaccination. Physicians should be aware of the possibility of cardiovascular complications after COVID-19 vaccination.